Pemberian Massage Pada Bayi Dan Anak Untuk Meningkatkan Kualitas Tidur Di Posyandu Balita Sejahtera Abadi - Shella Dhika Rahmawati; Ni Kadek Krisna Dwi Patrisia; Almita Ratu Rifanda; Sofia Mardiana; Friesca Persityara Agatha; Aulia Ayu Kusuma W (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Sleep is one of the needs of a baby or child that is as important as other main needs. One way to fulfill a baby's sleep needs is with massage (touch). Touching the skin will stimulate blood circulation and will increase the energy of oxygen waves which will be sent to the brain, thus encouraging the circulation and respiratory system to be better. The feeling of comfort and relaxation resulting from massage will improve sleep quality. Apart from that, it can increase breast milk production, increase body weight, increase endurance, in babies 0-6 months. The aim of this community service is to apply massage to improve the sleep quality of babies 0-6 months. The service method was carried out at the Balita Sejahtera Abadi Poyandu with 13 people in 1 group given intervention with baby massage. in normal babies 0-6 months. The conclusion of this service is that there is an effect of giving baby massage on the sleep quality of normal babies 0-6 months.